Modern clinical portrait of ovarian cancer patient in the Novosibirsk region - A. V. Tarkhov; M. A. Goncharov; A. V. Tereschenko; N. Yu. Zvezdina; N. A. Buksel; D. K. Ukolova; L. Yu. Konovalova; D. K. Nikitina; D. V. Morozov; M. S. Selyakova (Сибирский онкологический журнал)
Background. Ovarian cancer is one of the most common malignant neoplasms of the female genital area. In recent decades, there has been a change in the age composition of patients with ovarian cancer, a change in the nature of concomitant diseases, and an increase in the number of primary multiple malignant neoplasms. In this regard, it is necessary to assess clinical and epidemiological characteristics of patients with ovarian cancer and to compare them with literature data for timely diagnosis of the disease and increasing the effectiveness of treatment. Purpose of the study: to determine the current clinical characteristics of patients with ovarian cancer in the Novosibirsk region. Material and methods. A retrospective analysis of the medical records of 370 patients with newly diagnosed ovarian cancer, who were treated from 2020 to 2023 in the gynecological oncology department of the city clinical Hospital No. 1, was conducted. The study assessed the following parameters: age, gynecological history, body mass index, concomitant diseases, hereditary cancer history, presence of multiple primary malignant neoplasms, complaints, duration of the disease from the first clinical manifestations to morphological verification, assessment of the level of tumor markers CA-125 and HE-4, histological type of tumor, and stage of disease. Results. There were 69.2 % ovarian cancer patients aged over 50 years, 22.4 % patients aged 41–50 years, and 8.4 % patients aged under 40 years. More than half of the patients with ovarian cancer (56.2 %) either had no births at all (13.8 %) or had only one birth (42.4 %), while 68.2 % had a history of abortions. The comorbidities of arterial hypertension, diabetes mellitus, and obesity were common in ovarian cancer patients. A burdened family history of cancer was revealed in 42.2 % of patients. BRCA 1 and BRCA 2 mutations were found in 13.7 % of patients. in 66.8 % of cases, ovarian cancer was detected in an advanced stage (stage III–IV). High-grade serous ovarian carcinoma was the most common histological type. Primary complete or optimal cytoreductive surgery was performed in 82.7 % of patients with all stages of ovarian cancer. Conclusion. Comparison of modern clinical and epidemiological characteristics of ovarian cancer patients with available literature data makes it possible to more effectively determine risk factors, thereby increasing the quality of diagnosis and improving treatment outcomes.